(untitled) (مجلة الرازي الطبية, 2025)
Keratosis punctata of the palmar creases (KPPC) is a benign skin condition on the palms that manifests as small, thickened spots in the lines of the palms. We report a 45-year-old Libyan woman whose lesions began at age 12, with a positive family history and a 20-year history of treatment for presumed viral warts and other differential diagnoses. Early recognition of KPPC’s characteristic features can prevent unnecessary destructive treatments.